Integration of Digital Technology in Fiqh Learning: Analysis of Challenges and Effective Strategies - Najamudin Najamudin; Surahman Hidayat; M. Ulil Albab (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
Integration of digital technology in fiqh learning is an important aspect in the fast-paced information era, where access to educational materials is increasingly easy and diverse. This study aims to analyze the challenges faced in the application of digital technology in fiqh learning and identify effective strategies to overcome them. The research method used is a qualitative approach with literature studies and direct observation as the main data collection techniques. This study analyzes various academic sources, educational policy documents, and reports on fiqh learning practices that have implemented digital technology. In addition, observations were conducted at several fiqh educational institutions in Indonesia to understand the real context of technology application in learning. The results of the study indicate that the main challenges faced include lack of adequate training for teachers, inadequate technological infrastructure, and resistance to change from some parties. Nevertheless, the integration of digital technology has great potential in increasing student engagement and the effectiveness of fiqh learning. The proposed strategies include increasing ongoing training for teachers to improve digital skills, developing adaptive and responsive curricula to technological developments, and collaborating with third parties to provide necessary resources, such as learning software and applications. The conclusion of this study confirms that with the right approach, the integration of digital technology can enrich the experience of learning fiqh, improve understanding, and make fiqh materials more accessible. This study is expected to contribute to the development of more relevant and effective fiqh education in the digital era, as well as being a reference for educational policies that support technology integration.